2009
DOI: 10.1213/ane.0b013e3181b0cbea
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Exposure of the Operating Room Staff to Sevoflurane During Intracerebral Surgery

Abstract: The close proximity of the surgeon's breathing zone to the craniotomy window does not appear to be a source of increased exposure to sevoflurane. The observed higher exposure of the anesthesiologist to sevoflurane in the operating room environment warrants further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…to restore visibility), is therefore accompanied by the release of sevoflurane vapor. Hence, it is an additional source of waste anaesthetic gas (WAG) pollution [59,60,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. Known sources of WAG pollution include leakage from the patient's mask, from endotracheal coupling, from loose tube fittings and from air exhaled by the patient in the recovery room.…”
Section: Discussionmentioning
confidence: 99%
“…to restore visibility), is therefore accompanied by the release of sevoflurane vapor. Hence, it is an additional source of waste anaesthetic gas (WAG) pollution [59,60,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. Known sources of WAG pollution include leakage from the patient's mask, from endotracheal coupling, from loose tube fittings and from air exhaled by the patient in the recovery room.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have, indeed, indicated that operating room personnel are at risk from such increased occupational exposure. This risk is increased in situations of insufficient scavenging of waste gases and operating room ventilation and in situations where the operating room personnel work close to places where the spillage occurs 4,5,7,[17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric anesthesia with face masks, laryngeal masks or cuffless tracheal tubes significantly increase the concentration of anesthetic gases in the operating room [2,3]. In a recent study, Tankó et al revealed that during intracerebral surgeries, the evaporated amount of sevoflurane is the highest at the anesthetist's breathing zone, the most important source of this leakage is the patients' mouth [4] and the amount of evaporated gas is independent of the endotracheal tube cuff pressure [5]. It has been also demonstrated that exposure of the anesthesia staff can be decreased by proper positioning of the anesthesia personnel during intracranial surgery [6].…”
Section: How Can Anesthetic Gases Get Into the Air Of Operating Rooms?mentioning
confidence: 99%
“…There are three basic types of sample collection to assess work environment: personal, areal and source samples. Collection of personal samples is the best approach to measure the overall exposure of workers, because it represents gas concentrations of the worker's breathing zone the best during the period of sample collection [4]. This is actually the most preferred method to measure workers' average exposure per unit of time, both in operating theaters and in post-anesthetic care units.…”
Section: How To Monitor the Degree Of Halogenated Anesthetic Gas Expomentioning
confidence: 99%